First experimental results from the GPPD diffractometer at the CSNS. Issue 2 (3rd April 2018) - He, Lunhua; Chen, Jie; Lu, Huaile; Luo, Ping; Wu, Yaoda; Kang, Le; Zhang, Jiuchang; Zhang, Junrong; Du, Rong; Jia, Xuejun; Liang, Tianjiao; Wang, Fangwei
ABSTRACT: The general purpose powder diffractometer (GPPD) is the first powder diffractometer at the China Spallation Neutron Source (CSNS). Its aim is to provide a high-resolution, good-intensity instrument for users to study crystallographic and magnetic structures. The best resolution will be better than 0.2% at high-angle detector bank. The neutron flux at the sample position will be at the order of 10 7 n/s/cm 2 . The joint beam commissioning among accelerators, target station and instruments started in the CSNS on November 1, 2017. The neutron beam shutter for the general purpose powder diffractometer (GPPD) was opened for the first time. Initial measurements and standard sample diffraction experiments are reported, which are used to characterize the instrument performance. It is shown that the results agree well with the design goal. During the commissioning, a series of user experiments have been conducted. Two user experimental results have already been published.